Gerakan Remaja Peduli Anemia - Satiyem Satiyem; Dewi Murtiningsih (Jurnal Pengabdian Masyarakat Jajama (JPMJ), 2025)
Anemia in adolescents is not only felt during adolescence, but will continue into adulthood which in the future will experience pregnancy and childbirth. Therefore, preventive and promotive actions are needed to prevent anemia in adolescents, as well as to reduce the incidence of anemia. One of the promotive efforts that can be implemented is by empowering adolescents with the Anemia Care Youth Movement. The method used is to conduct early detection and direct health education to adolescents. Health education and early detection of anemia were carried out at the Jetis Village Hall in Jaten District, Karanganyar and attended by 35 adolescents. The media used were booklets, power points, hemoglobin checkers and loudspeakers. The results of early detection of anemia in adolescents showed that 35% of adolescents had anemia with an average of 11 gr/dl, and the results of health education showed an increase in knowledge regarding the definition, classification, signs and symptoms, causes, impacts, how to prevent and treat anemia. Adolescents were also given iron tablets and a control book on compliance with iron tablet consumption with the aim of preventing and overcoming anemia in the Jetis Village environment.